2004
DOI: 10.1111/j.1600-0625.2004.00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Androgen action on human skin – from basic research to clinical significance

Abstract: Androgens affect several functions of the human skin, such as sebaceous gland growth and differentiation, hair growth, epidermal barrier homeostasis and wound healing. Their effects are mediated by binding to nuclear androgen receptors. Androgen activation and deactivation are mainly intracellular events. They differ from cell type to cell type and between cells at different locations. The major circulating androgens, dehydroepiandrosterone sulfate and androstenedione, are predominantly produced in the adrenal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(112 citation statements)
references
References 50 publications
(71 reference statements)
3
103
0
6
Order By: Relevance
“…(6,7,20,24,51,70,(72)(73)(74)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95). These studies indicate that human hair follicles are also peripheral endocrine mini-organs that are both a source (including a metabolizing source) and a target of multiple neuro-steroido-hormones (4,74,91,(95)(96)(97)(98). This endocrine capacity resides in the main cell populations of the hair follicle (keratinocytes, melanocytes and fibroblasts).…”
Section: Overviewmentioning
confidence: 97%
“…(6,7,20,24,51,70,(72)(73)(74)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95). These studies indicate that human hair follicles are also peripheral endocrine mini-organs that are both a source (including a metabolizing source) and a target of multiple neuro-steroido-hormones (4,74,91,(95)(96)(97)(98). This endocrine capacity resides in the main cell populations of the hair follicle (keratinocytes, melanocytes and fibroblasts).…”
Section: Overviewmentioning
confidence: 97%
“…Additionally, it was reported that an elevation in the PGF-β level leads to granulation tissue formation [7]. The role of hormonal factors in wound healing during the prepubertal period and post-pubertal period has also been investigated [8]. Androgens are known to play a role in pro-inflammatory and anti-inflammatory pathways, both on a systemic level and cellular level [9].…”
Section: Discussionmentioning
confidence: 99%
“…피지샘의 피지세포는 squalenes, wax ester, cholesterol ester를 함유하는 피지(sebum lipids)를 분비함으로써 [42] 지 질층을 형성하여 유해화학약품, UV, 미생물로부터 피부를 보호하고 [33], Vitamin E를 분비하여 산화손상 [35]을 막고 palmitoleic acid [39] 및 defensin, cationic protein을 분비 [26], histone H2A와 H2B, 다른 cationic protein 등을 분비하 여 [5] 항박테리아 기능을 한다. 또한 피지세포는 국소 내분비 세포의 기능과 glycoconjugates를 함유하고 있다 [43].…”
Section: 서 론unclassified